Tendencje w poziomie i zróżnicowaniu wynagrodzeń w Polsce po przystąpieniu do Unii Europejskiej - Adamczyk, Piotr (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
The article presents the changes in the level of wages in Poland after its accession into EU. The aim of the research was to estimate the diversity rate of the wages in regional and professional context. The author used the data from the Central Statistical Office and the coefficient of variation. It was stated that within the years 2004–2007 the real wage increased in all voivodships and sectors of national economy. It was also observed that disproportion in the level of wages occurred before 2004 was decreasing slowly